Imaging the tarsal plate: A Mini-Review - Recchioni, Alberto (Scandinavian Journal of Optometry and Visual Science, 2021)
Imaging the tarsal plate and the meibomian glands (MG) grants new opportunities for ophthalmic practitioners who work in the field of the ocular surface and dry eye across the globe. The secretory role of MG plays a fundamental part in protecting the moisture in front of the eye surface by creating an active shield made of meibum (lipid) which prevents tear evaporation and causes dry eye. Evidence from the most popular Dry Eye Workshop reports (2007 and 2016) demonstrate that MG dysfunction is the first cause of evaporative dry eye which is also the most common cause of dry eye and ocular surface discomfort. Fortunately, during the last years, a plethora of new devices for MG observation, diagnosis and follow-up have been made available in the market. These devices range from invasive to minimally invasive, high to low-tech and from being expensive to low-cost. The objective of this mini-review is to condense the latest evidence in MG imaging by providing a narrative overview on the most common technologies plus some other newer aspects which might guide clinicians and researchers in the field of the ocular surface and dry eye.